Kønnets regerende dronning - en introduktion til køn og krop i Judith Butlers forfatterskab - Stormhøj, Christel (Kvinder, Køn & Forskning, 1999)
This article introduces the work of Judith Butler, whose theory of gender performativity has become highly influential in contemporary studies of gender and sexuality. Her main thesis is that both gender and sex are produced by discourse. In order to deal with the discursive construction of bodies, it is necessary to move beyond the opposition between sex and gender long upheld in feminist theory. Butler’s theory is intended as an improvement on constructionism. Understanding construction as involving the materialization of determinate types of bodies through the iteration of gender-constituting performatives, she argues that both sex and gender are co-original effects of this process. The function of performatives is to create heterosexually structured bodies and subjects, and these performatives operate by prescribing other identifications. Because there is never any easy fit between the stream of identifications and desires and the performativity of prescribtions and proscribtions, identities are always phantasmatic. The constitution of a heterosexually organized, gender differentiated identity rests on that which has been excluded and abjection figures as a critical resource on the struggle to rearticulate the terms of symbolic intelligibility and legitimacy in Butler’s political vision.